PENGARUH ATRIBUT PRODUK, SWITCHING COST, KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN (Studi Pada Pengguna Vivo Pada Masyarakat Di Surakarta) - Riani, Alfina; Susanti, Ari (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to see the Effect of Product Attributes, Switching Costs, and Consumer Satisfaction on Customer Loyalty. The data was collected through the distribution of an online questionnaire to vivo users in Surakarta and which will be a sample of 96 respondents. The data obtained will be processed using several tests, such as data instrument test, classical assumption test, multiple regression analysis, t-test, f test, and coefficient of determination processed using the SPSS application. The results of the study proved that the variables of Product Attributes, Switching Cost, and Consumer Satisfaction had a positive and significant effect on Customer Loyalty.Keywords: Product Attributes, Switching Cost, Consumer Satisfaction, Customer Loyalty.